2008
DOI: 10.1093/jn/138.7.1336
|View full text |Cite
|
Sign up to set email alerts
|

Cis-9, trans-11-Conjugated Linoleic Acid Inhibits Allergic Sensitization and Airway Inflammation via a PPAR γ-Related Mechanism in Mice3

Abstract: Milk consumption from early childhood on has been found to be inversely correlated with allergic sensitization and the onset of bronchial asthma. We tested whether cis-9,trans-11-conjugated linoleic acid (c9,t11-CLA), naturally occurring in milk fat, may prevent allergic sensitization and inhibit airway inflammation in a murine asthma model. BALB/c mice were fed a diet enriched in 1 wt% of c9,t11-CLA or a control diet 7 d prior to and for 32 d during sensitization [d 1 and 14, 100 mg/L ovalbumin (OVA) in adjuv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 48 publications
3
73
0
1
Order By: Relevance
“…In contrast to our results, Whigham et al [42] observed a decrease in inflammatory eicosanoid mediators in comparison to the basal release of eicosanoids in CLA-supplemented animals when respiratory organs were challenged with OVA ex vivo. Furthermore, Jaudszus et al [18] showed that dietary CLA supplementation of mice with a synthetic FA affects sensitization and is capable of reducing the release of the proinflammatory cytokine IL-5. Our experiments, applying CLA in a natural matrix revealed no decrease in T H 2 cytokines in milk diet-fed animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, Whigham et al [42] observed a decrease in inflammatory eicosanoid mediators in comparison to the basal release of eicosanoids in CLA-supplemented animals when respiratory organs were challenged with OVA ex vivo. Furthermore, Jaudszus et al [18] showed that dietary CLA supplementation of mice with a synthetic FA affects sensitization and is capable of reducing the release of the proinflammatory cytokine IL-5. Our experiments, applying CLA in a natural matrix revealed no decrease in T H 2 cytokines in milk diet-fed animals.…”
Section: Discussionmentioning
confidence: 99%
“…Another placebo-controlled study conducted in allergic patients revealed that oral CLA supplementation improved symptoms and immunological parameters during pollen season [17]. In line with these findings an experimental approach in a murine model of asthma where mice were fed a synthetically produced CLA derivate underlined that dietary CLA uptake might lead to allergoprotection [18]. …”
Section: Introductionmentioning
confidence: 88%
“…Although cis-9, trans-11-conjugated linoleic is not contained in the experimental diet used in this study, it has been reported that cis-9, trans-11-conjugated linoleic exerts anti-inflammatory effects in vivo. A recent study by Jaudszus et al shows that cis-9, trans-11-conjugated linoleic acid reduces IgE production and allergen-induced airway hyperresponsiveness (12). Furthermore, bovine milk fat enriched in cis-9, trans-11-conjugated linoleic also reduces circulating allergen-specific IgE and IgG1 levels in OVA-immunized C57BL/6 mice (13).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study demonstrating the in vitro anti-allergic effect of CLNAs on HMC-1 cells, and this is in line with earlier findings showing that CFAs, such as CLAs, may possess anti-allergic activities. For example, Jaudszus et al (24) reported that 9Z, 11E-CLA could inhibit allergic sensitization and airway inflammation through peroxisome proliferator-activated receptor-γ dependent mechanism in mice, whereas others demonstrated that human healthy volunteers supplemented with 9Z, 11E-CLA resulted in a decreased plasma IgE level and reduced secretion of IL-5 by PBMCs (25,26). Despite these earlier findings, the underlying action mechanisms for the anti-allergic effects of CFAs, such as CLAs and CLNAs, remain poorly understood and further studies are required to elucidate the mechanisms, in vitro and in vivo, for the anti-allergic activity of CFAs.…”
Section: A B C Dmentioning
confidence: 99%